Habilidades blandas requeridas por los estudiantes de la carrera de Gestión del Talento Humano para ingresar al mercado laboral - Montes Reina, Andrea Mishell (2024)
The growing emphasis on the demand for highly skilled professionals, not only in terms of technical competencies but also soft skills, plays a crucial role in the dynamic contemporary work environment. This context, this research project focuses on the topic "Soft Skills Required by Students in Human Talent Management Programs to Enter totheJob Market," with the general purpose toidentify the needs for these skills in the workplace. Methodologically, a quantitative approach focused on the measurement and quantification of phenomena was employed, with a non-experimental design as direct manipulation of interest variables, and with a descriptive scope for data analysis and interpretation. The main used technique was a survey, which allowed precise data collection from involved participants in the issue, specifically human talent area collaborators responsible for recruitment and selection process in organizations. To assess reliability of theusedquestionnaire, the Cronbach's Alpha coefficient was applied, obtaining a value of 0.828, suggesting high scientific validity of the usedinstrument. The findings reveal significant importance of soft skills, among which critical thinking (70%), stress management (53.3%), decision making (36.7%), change management (63.3%), and resilience (46.7%) stand out. Additionally, a positive perception regarding the development of these skills in future professionals is observed. In the work context, the relevance of soft skills in long-term strengthening and success is emphasized, evidenced by their consideration as a highly important aspect in the selection process, with 40% of respondents, highlighting their crucial role.